A Review of “Rational Theology in Interfaith Communication” by Wilferd Madelung and Sabine Schmidtke - Halil İbrahim Delen (Darulfunun Ilahiyat)
Madelung, W., & Schmidtke, S. (01 Sep. 2006). Rational Theology in Interfaith Communication. Leiden, The Netherlands: Brill.